Microwave-assisted synthesis of a novel CuC2O4∙xH2O/Graphene composite as anode material for lithium ion batteries. Issue 1 (January 2020) - Zhang, Chi; Zheng, Binfeng; Song, Zhi; Shi, Shaojun; Mao, Han
Abstract: Transition metal oxalates are considered promising candidates for anode materials of lithium ion batteries. However, they suffer from volume effect similar to that of transition metal oxides, which leads to poor cycle stability. In this study, CuC2 O4 ∙xH2 O/graphene composite has been synthesized by a facile microwave-assisted hydrothermal process at low temperature. X-ray diffraction (XRD) patterns of the composite indicate that CuC2 O4 ∙xH2 O was the main phase with no impure peak observed. The graphene peak was also not detected. The SEM images indicated that the CuC2 O4 ∙xH2 O cube was uniformly compositing with the graphene sheets. Larger surface area with porosity is obtained with a weigh amount of 5.42 wt% for graphene. Therefore, excellent electrochemical properties were obtained with a high reversible discharge/charge capacity of 1043/1013 mAh g −1 after 100 cycles. The capacity was also found to continually increase during the initial cycles. In addition, high discharge/charge capacities of 952/949, 719/720, and 535/533 mAh g −1 were obtained at current densities of 0.5, 1.0, and 2.0 A g −1, respectively. Cyclic voltammetry (CV) was also performed to further investigate the electrochemical reactions of CuC2 O4 ∙xH2 O/GO, especially during the initial cycles.